"Sense of effort" and M1 activity with special reference to resistance exercise with vascular occlusion - Yudai Takarada (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Low-to-moderate intensity resistance exercise with vascular occlusion induces increased muscle mass and strength, comparable to that after conventional heavy resistance training. Also, participants feel as if they require greater force (effort) to lift a weight when undergoing resistance exercise following vascular occlusion. Vascular occlusion of the proximal upper arm increased perceived magnitude of exerted hand-grip force without causing any accompanying changes either in electromyographic or efferent/afferent activity of the median nerve. There was also no effect on motor evoked potentials in the hand following resting-state transcranial magnetic stimulation (TMS) over the primary motor cortex (M1). Moreover, low-frequency, repetitive transcranial magnetic stimulation (lf-rTMS) over the left primary somatosensory cortex did not significantly affect estimations of right-hand grip force exertion. Thus, the primary factor responsible for the overestimation of force exertion with increased voluntary effort ("sense of effort") during occlusion was the central signal related to motor command size. Brain imaging studies show that vascular occlusion increases M1 activity during force exertion, which may be related to functions of motor-related cortical areas, e.g., supplementary motor area, as sources of excitatory input to M1. M1 suppression by lf-rTMS during force exertion causes participants' sense of effort and force perception to increase. This mechanism may also operate during muscular contraction with vascular occlusion. It is easy to imagine perceiving maximal effort when we consciously try to produce maximal force; however, does M1 activity become maximal at that point in time? In this study, the liberation of potential muscular strength, focusing on the motor system state before awareness of motor intention, is looked at.